A novel cell-free system reveals a mechanism of circular DNA formation from tandem repeats - Cohen, Sarit (Oxford University Press, 2001)
One characteristic of genomic plasticity is the presence of extrachromosomal circular DNA (eccDNA). High levels of eccDNA are associated with genomic instability, exposure to carcinogens and aging. We have recently reported developmentally regulated formation of eccDNA that occurs preferentially in  pre-blastula Xenopus laevis embryos. Multimers of tandemly repeated sequences were over-represented in the circle population while dispersed sequences were not detected, indicating that circles were not formed at random from any chromosomal sequence. Here we present detailed mechanistic studies of eccDNA formation in a cell-free system derived from Xenopus egg extracts. We show that naked chromosomal DNA from sperm or somatic tissues serves as a substrate for direct tandem repeat circle formation. Moreover, a recombinant bacterial tandem repeat can generate eccDNA in the extract through a de novo mechanism which is independent of DNA replication. These data suggest that the presence of a high level of any direct tandem repeat can confer on DNA the ability to be converted into circular multimers in the early embryo irrespective of its sequence and that homologous recombination is involved in this process.